If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(x + 2) + 4 = -6 Reorder the terms: -5(2 + x) + 4 = -6 (2 * -5 + x * -5) + 4 = -6 (-10 + -5x) + 4 = -6 Reorder the terms: -10 + 4 + -5x = -6 Combine like terms: -10 + 4 = -6 -6 + -5x = -6 Add '6' to each side of the equation. -6 + 6 + -5x = -6 + 6 Combine like terms: -6 + 6 = 0 0 + -5x = -6 + 6 -5x = -6 + 6 Combine like terms: -6 + 6 = 0 -5x = 0 Solving -5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-5'. x = 0 Simplifying x = 0
| 6y=8-(9-6y) | | 12+24/2 | | 251/4-205/6= | | R^3=109.2 | | 6+24/2 | | 12*y=384 | | 2-5x+6=-18 | | (2x+1)^1/3=5 | | 455.9=1.33(3.14)r^3 | | 79/24+2/3n-11/4n=5/2+1 | | 3x-6x-9=-3x+7-9 | | -9x^2+18x=16 | | 7(3x-4)=8(x-6)+10 | | 18/24908 | | 0.3x-5=1.1x-17 | | 2(3p-4)=46 | | (2x+1)1/3=5 | | 5p=-6 | | 24908/18 | | 4/3(3.14)=x | | u=6+t | | 2.50=x/(48-x) | | 455.9=4/3(3.14)r^3 | | -7(x+3)-42=4-11 | | y=5+-12 | | -3p+8p= | | y+3=-2(x)-1 | | 8-17/x=4+3/x | | 747+(-6x)=300 | | 3(x+1)-1=3x-2 | | (3/5)x^2-7x-20=0 | | 77(5/9)=x |